Sladkorna bolezen tip 1 in psihosocialni dejavniki tveganja v mladostništvu - Drobnič Radobuljac, Maja (Zdravniški vestnik, 2012)
Type 1 diabetes is one of the more common chronic conditions in childhood and adolescence. It is an autoimmune disorder that leads to destruction of beta cells in the pancreas and consequently hyperglycemia. Presently, approximately700 children, adolescents and students up to the age of 25 years from entire Slovenia are followed up for type 1 diabetes. In young people withchronic disease adolescence itself often causes complications in the course of the disease. The risk of complications is even higher in the presence of various psychosocial risk factors. The present article focuses on the prevalence and the influence of risk-taking behavior, mental disorders andsuicidal behavior on the course and management of type 1 diabetes in adolescence and summarizes the latest clinical guidelines for the management of adolescents with these comorbidities.
Keywords: Adolescenca; Adolescence; Adolescent Behavior; Adolescentno vedenje; Alcohol Drinking; Alkohol, pitje; child; dejavniki tveganja; Diabetes Mellitus, Insulin-Dependent; Eating Disorders; Hiperglikemija; Hranjenje, motnje; Hyperglycemia; Kajenje; mladostniki; Nedovoljene snovi; otroci; Practice Guidelines; Praktična navodila; psihosocialni dejavniki tveganja; Samomor; sladkorna bolezen; Sladkorna bolezen inzulin-odvisna; Smoking; Street Drugs; Suicide; tvegana vedenja